The use of the Lean Method and Failure Mode and Effects Analysis (FMEA) on Product Costing - An Implementation in Automotive Battery Manufacturing - Vega Prasetyo; Jani Rahardjo (International Journal of Industrial Research and Applied Engineering, 2020)
This paper reporst a research that was conducted to utilize lean method and failure mode and effects analysis (FMEA) in product costing, in order to obtain more rational price standard. FMEA as one of the methods to analyze risks is used in this paper as a tool to identify the risks from the waste side which is then adapted into a product costing in order to obtain a more rational product price structure. Utilizing both methods produce a waste priority number with adjustment value of 52.23% to the existing product cost. This adjustment makes the cost of product higher than before but yields less gap with the highest retail price